[OP.5B.09] RELATIONSHIP BETWEEN RENAL HEMODYNAMICS AND CORONARY ATHEROSCLEROTIC BURDEN IN PATIENTS WITH HYPERTENSION. (September 2017) - Geraci, G.; Mule', G.; Buccheri, D.; Di Natale, K.; Scaduto, E.; Zammuto, M.; Nardi, E.; Geraci, C.; Piraino, D.; Andolina, G.; Cottone, S.
Abstract : Objective: Cardiovascular diseases recognize ischemia as the main pathogenetic prime mover and represent the final step of morphofunctional vascular changes that develop over a long period of time, mostly asymptomatically. Recent studies detected the role of intrarenal hemodynamic changes as independent predictors of cardiovascular events in different populations. No data exist about the relationship between renal hemodynamics and coronary atherosclerotic damage. The purpose of our investigation is to study the relationship between intrarenal vascular changes and coronary atherosclerotic burden in hypertensive patients. Figure. No caption available. Design and method: We enrolled 130 hypertensive subjects (30–80 years) who received indication for elective coronary angiography. Duplex ultrasound of intrarenal vasculature was performed to evaluate renal resistive index (RI), renal pulsatility index (PI) and renal acceleration time (AT). Subsequently, a coronary angiography was performed to assess atherosclerotic burden through Gensini Score (GS). Carotid intima-media thickness (cIMT) was also assessed as a model of vascular damage well related with renal parameters. The population was divided into quintiles based on the GS (I quintile: GS < 9; II quintile: GS>9 and <17; III quintile: GS>17 and <30.8; IV quintile: GS>30.8 and <44; V quintile: GS>44). Statistical analysis was also performed in the population divided in 2 groups: 1) subjects with mild coronary disease (GS<30); 2) subjects with severe coronary disease (GS>30). Results: Subjects in higher quintiles had greater values of PI, RI and lower values of AT compared to the ones in lower quintiles. The correlation between GS and PI, RI or AT was not statistically significant at the univariate analysis in overall population, whereas GS, IR and IP were significantly associated with cIMT (all p < 0.01). IP and IR, but not AT, were associated to GS in the group with GS<30, whereas did not correlate in subjects with GS>30. These correlations held after adjustment for multiple confounders. Conclusions: Renal vascular changes are not significantly related to coronary atherosclerotic burden in all hypertensive patients. Nevertheless, within the complex mathematical relationship between PI (or RI) and GS (Figure 1), the relationship becomes linear and significant in patients with mild coronary disease.